NIKAH SIRRI DAN ISTBAT NIKAH DALAM PANDANGAN LEMBAGA BAHTSUL MASAIL PWNU YOGYAKARTA - Masduqi, Irwan (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
This article will address the terminology of sirrimarriages, which has been completely misinterpreted in Indonesia. Besides attempting to clarify this terminological problem, this paper will also discuss the debate on the law of sirrimarriages through the perspectives of classical and contemporary ulamas who have become the source for consideration for activists from BahtsulMasail PWNU Yogyakarta in reacting to this issue. A discussion no less important is the proposal for a new fiqhon marriage (fiqh al-munakahah al-jadidah) recommending the registration of marriage as an extra requirement of the validity of marriage. This paper will offer a solution to address the legal conundrum surrounding Law No. 50 of 2009 and Article 7(3) of the Compilation of Islamic Law, which regulates a court’s right to legalize marriages (marital itsbat) prior to the enforcement of Law No. 1 of 1974, whereas many of such requests for itsbat are done for cases of unregistered polygamy after the enactment of Law No. 1 of 1974.